Apoptosis and cell proliferation during metamorphosis of the planula larva of Clytia hemisphaerica (Hydrozoa, Cnidaria). Issue 12 (3rd June 2021) - Krasovec, Gabriel; Pottin, Karen; Rosello, Marion; Quéinnec, Éric; Chambon, Jean‐Philippe
Abstract: Background: Metamorphosis in marine species is characterized by profound changes at the ecophysiological, morphological, and cellular levels. The cnidarian Clytia hemisphaerica exhibits a triphasic life cycle that includes a planula larva, a colonial polyp, and a sexually reproductive medusa. Most studies so far have focused on the embryogenesis of this species, whereas its metamorphosis has been only partially studied. Results: We investigated the main morphological changes of the planula larva of Clytia during the metamorphosis, and the associated cell proliferation and apoptosis. Based on our observations of planulae at successive times following artificial metamorphosis induction using GLWamide, we subdivided the Clytia 's metamorphosis into a series of eight morphological stages occurring during a pre‐settlement phase (from metamorphosis induction to planula ready for settlement) and the post‐settlement phase (from planula settlement to primary polyp). Drastic morphological changes prior to definitive adhesion to the substrate were accompanied by specific patterns of stem‐cell proliferation as well as apoptosis in both ectoderm and endoderm. Further waves of apoptosis occurring once the larva has settled were associated with morphogenesis of the primary polyp. Conclusion: Clytia larval metamorphosis is characterized by distinct patterns of apoptosis and cell proliferation during the pre‐settlement phase and the settled planula‐to‐polyp transformation. Key Findings: Here, we described for the first time the dynamics process of the larva metamorphosis of the well‐established model of cnidarian Clytia hemisphaerica at the morphological and cellular scale. This fundamental descriptive work brought out that metamorphosis start before the settlement, in opposite with the usually accepted view in marine animals. At the cellular level we characterized apoptosis, proliferation and migration implicated in major transformations. One of them is the adhesive structure offset laterally, an unexpected characteristic in a cnidarian.